Influence of negative ions on atomic oxygen production in a hollow cathode discharge in O₂/Ar mixture - Lavrukevich, Yu.; Ryabtsev, A.; Tsiolko, V. (Вопросы атомной науки и техники, 2017)
The main mechanisms for atomic oxygen generation in a discharge with a hollow cathode in Ar/O₂ mixture were found. It was shown that for different oxygen concentrations the different reactions are responsible atomic oxygen formation. At higher oxygen concentration in the mixture negative ions play a significant role in the formation of atomic oxygen. This property of the discharge is due to the low electric field in the working volume, and consequently low electron temperature. Выявлены основные механизмы генерации атомарного кислорода в разряде с полым катодом в смеси O₂/Ar. Было показано, что при различных концентрациях кислорода в разряде за образование атомарного кислорода отвечают различные реакции. При высокой концентрации кислорода в смеси в формировании атомарного кислорода играют значительную роль негативные ионы. Это свойство разряда обусловлено низким значением электрического поля в рабочем объёме, а следовательно, низкой электронной температурой. Виявлено основні механізми генерації атомарного кисню в розряді з порожнистим катодом в суміші O₂/Ar. Було показано, що при різних концентраціях кисню в розряді за утворення атомарного кисню відповідають різні реакції. При високій концентрації кисню в суміші у формуванні атомарного кисню відіграють значну роль негативні іони. Ця властивість розряду зумовлена низьким значенням електричного поля в робочому об'ємі, а отже, низькою електронною температурою.